2020
DOI: 10.1016/j.nmni.2020.100756
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary report of in vitro and in vivo effectiveness of dornase alfa on SARS-CoV-2 infection

Abstract: Dornase alfa, the recombinant form of the human DNase I enzyme, breaks down neutrophil extracellular traps (NET) that include a vast amount of DNA fragments, histones, microbicidal proteins and oxidant enzymes released from necrotic neutrophils in the highly viscous mucus of cystic fibrosis patients. Dornase alfa has been used for decades in patients with cystic fibrosis to reduce the viscoelasticity of respiratory tract secretions, to decrease the severity of respiratory tract infections, and to improve lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 41 publications
2
43
0
Order By: Relevance
“…DNases can efficiently destroy NETs, and therefore clinical trials applying DNase treatment as potential therapeutic intervention in severe COVID-19 patients may be warranted (51). Furthermore, treatment strategies with dornase alfa to destroy NETs in COVID-19 patients with ARDS are already investigated in clinical trials (27,51). Here we confirmed in a control experiment, that ex vivo nuclease treatment of lung biopsies from SARS-CoV-2-infected hamster successfully degraded present NETs (Figure 5).…”
Section: Endothelialitis and Vasculitis In Lungs Of Golden Syrian Hamsupporting
confidence: 67%
See 1 more Smart Citation
“…DNases can efficiently destroy NETs, and therefore clinical trials applying DNase treatment as potential therapeutic intervention in severe COVID-19 patients may be warranted (51). Furthermore, treatment strategies with dornase alfa to destroy NETs in COVID-19 patients with ARDS are already investigated in clinical trials (27,51). Here we confirmed in a control experiment, that ex vivo nuclease treatment of lung biopsies from SARS-CoV-2-infected hamster successfully degraded present NETs (Figure 5).…”
Section: Endothelialitis and Vasculitis In Lungs Of Golden Syrian Hamsupporting
confidence: 67%
“…The detected microvascular injury during SARS-CoV-2-infections can at least partially be explained by these findings and is substantiated by recent observations of increased NET markers in the blood of SARS-CoV-2 patients (23). DNases can efficiently destroy NETs, and therefore clinical trials applying DNase treatment as potential therapeutic intervention in severe COVID-19 patients may be warranted (51). Furthermore, treatment strategies with dornase alfa to destroy NETs in COVID-19 patients with ARDS are already investigated in clinical trials (27,51).…”
Section: Endothelialitis and Vasculitis In Lungs Of Golden Syrian Hammentioning
confidence: 65%
“…No evidence has so far been provided about the presence of NETs in the lungs and their involvement in causing ARDS in COVID-19. Two recent reports also found DNase to be beneficial in COVID-19 69 , 70 . Weber et.…”
Section: Discussionmentioning
confidence: 89%
“… 135 ), reducing the risk for secondary infections and improving ventilation, and may also reduce the risk of progression towards ARDS, as shown in animal models 136 , 137 . Two case studies have shown that administration of dornase alpha is well tolerated in patients with COVID-19-associated ARDS 138 , 139 , and several trials are underway to determine the efficacy of this approach (NCT04402944, NCT04355364, NCT04432987, NCT04359654, NCT04445285, NCT04402970). Nebulizer administration of DNase provides direct access to NETs within the alveolar space, but there may be a barrier to reaching systemic efficacy owing to the high reported levels of platelet factor 4 (PF4) in severe COVID-19 (ref.…”
Section: Thrombosis Management In Covid-19mentioning
confidence: 99%